In silico enzyme screening identifies an SDR ketoreductase from Thermus caliditerrae as an attractive biocatalyst and promising candidate for protein engineering - Sosa, Yvett; Kapur, Bhav; Hurtak, Jessica; Kingsley, Laura J.; Wu, Hao; Gruber, Stefanie; Nar, Herbert; Khattabi, Saad; Moral, Jesus Seco; Lucas, Maria Fátima; Martin, Caterina; Lončar, Nikola; et al. (Frontiers in Chemical Biology, 2024)
Introduction: Biocatalysis, particularly through engineered enzymes, presents a cost-effective, efficient, and eco-friendly approach to compound synthesis. We sought to identify ketoreductases capable of synthesizing optically pure alcohols or ketones, essential chiral building blocks for active pharmaceutical ingredients. Methods: Using BioMatchMaker®, an in silico high-throughput platform that allows the identification of wild-type enzyme sequences for a desired chemical transformation, we identified a bacterial SDR ketoreductase from Thermus caliditerrae, Tcalid SDR, that demonstrates favorable reaction efficiency and desired enantiomeric excess. Results: Here we present two crystal structures of the Tcalid SDR in an apo-form at 1.9 Å and NADP-complexed form at 1.7 Å resolution (9FE6 and 9FEB, respectively). This enzyme forms a homotetramer with each subunit containing an N-terminal Rossmann-fold domain. We use computational analysis combined with site-directed mutagenesis and enzymatic characterization to define the substrate-binding pocket. Furthermore, the enzyme retained favorable reactivity and selectivity after incubation at elevated temperature. Conclusion: The enantioselectivity combined with the thermostability of Tcalid SDR makes this enzyme an attractive engineering starting point for biocatalysis applications.